Asia Pacific Tourism Trends: Is the Future Ours to See?. Issue 10 (2nd October 2016) - Tolkach, Denis; Chon, Kaye K.S.; Xiao, Honggen
ABSTRACT: This paper explores current and emerging tourism trends in the Asia Pacific region via content analysis of industry publications and subsequent review of related academic literature. Experience economy and activity-oriented travel lead the development of the sector in the region and impact other trends. Economic growth, favourable political environment and improved infrastructure have sustained continual growth in visitor numbers from long-haul and intra-regional markets. However, the profile of travellers and their interests are increasingly diverse. Additionally, technology has been playing a significant role in hospitality and tourism industries, while human resources remain one of the biggest challenges in the region. Despite the huge increase in academic literature on sustainability, the industry has not appeared to be engaged with the subject. A number of knowledge gaps are identified for future research to better understand tourism development in the Asia Pacific region.